Manajemen Laba: Pengaruh Keahlian Keuangan Komite Audit dan Gender - Shofia Salsabila; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2021)
The purpose of this study is to see how the influence of the audit committee’s financial expertise and gender on earnings management. The type of associative research is used in this study. Manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019 were selected in this study. The sample in this study was selected through the purposive sampling method and obtain 153 observations. Earnings management as dependent variable is measured using discretionary accrual by modified jones model (1991). the measurement of independent variable audit committee financial expertise used the percentage of audit committee with financial expertise, while gender is measured using dummy variable. The result of this study found that audit committee’s financial expertise and gender havo no significant effect on earnings management.